2001
DOI: 10.1177/109019810102800609
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Community Involvement to Organizational-Level Empowerment: The Federal Healthy Start Experience

Abstract: This article presents findings of a multisite case study of the experience of nine federal Healthy Start Program sites in using consortia and other community involvement strategies in the fight against infant mortality. Using empowerment theory as a conceptual framework, qualitative data are employed to examine how community involvement in the program through community-based consortia and other means contributed to empowerment at the organizational level. The article concludes with implications of the study fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 25 publications
2
50
0
2
Order By: Relevance
“…49,121 A key management strategy in this regard is to involve a broad and diverse array of participants in all decision making. Another is to make all of the leaders, staff, lead agencies, and fiscal agents formally accountable to the decision-making body of the collaboration rather than to their own employer or board.…”
Section: Promote Broad and Active Participationmentioning
confidence: 99%
“…49,121 A key management strategy in this regard is to involve a broad and diverse array of participants in all decision making. Another is to make all of the leaders, staff, lead agencies, and fiscal agents formally accountable to the decision-making body of the collaboration rather than to their own employer or board.…”
Section: Promote Broad and Active Participationmentioning
confidence: 99%
“…Interestingly in the current study, leadership was not found to predict perceived effectiveness or intrapersonal PE directly. In previous studies, leadership has been found to be an organizational characteristic that predicted PE (Maton, 2008;Minkler, Thompson, Bell, & Rose, 2001). More consistent with the current study's finding of the indirect relationship between leadership and intrapersonal PE, Hardina (2005) argued that empowerment-oriented leadership allowed for more staff opportunities and social support and, then related to such outcomes as improved service delivery and successfully advocating for social change.…”
Section: Discussionmentioning
confidence: 99%
“…11 Given the success of CBPR methods to reduce disparities, 12 organizations like the National Healthy Start Program (NHSP) have welcomed CBPR as a useful model for organizational empowerment among diverse stakeholders in settings where recognized methods for evaluation and program design have previously fallen short. 13,14 Might a CBPR approach, fostering a co-developed rather than an imposed solution, overcome perceived barriers to the adoption of SDM? An example of one such co-developed solution could be a decision support tool that serves the needs of the patient and physician by promoting collaboration within the clinical encounter rather than outside it.…”
Section: Community-based Participatory Research-a Potential Solutionmentioning
confidence: 99%